FUEL PROPERTIES OF FOREST RESIDUES RECOVERED FROM FULL EUCALYPTUS TREE HARVESTING IN DIFFERENT CHIP PRODUCTION SCENARIOS - Prates, Eloise; Lopes, Eduardo da Silva; Rodrigues, Carla Krulikowski; da Silva, Dimas Agostinho; da Silva, Matheus Kaminski Cândido (Floresta, 2023)
This study aims to evaluate the fuel properties of forest residues recovered from Eucalyptus saligna and E. urophylla × E. grandis stands at seven years old in five chip production scenarios. A forest inventory was conducted to estimate the dry biomass, followed by full-tree harvesting with minimum stem diameters equal to 8, 10, 12, and 14 cm for pulpwood, as well as the full trees for energy purposes (treatments). Moisture, volatile matter, fixed carbon, ash contents, and higher and lower heating values of chips were evaluated. The dry biomass was compared between stands by the t-test (α = 0.05) and the fuel properties were assessed between minimum stem diameters in the same forest stand by the Tukey’s test (α = 0.05). Higher chip moisture was obtained in the larger minimum stem diameter, since it showed an increased up to 88% in moisture for the E. urophylla × E. grandis stand. Volatile matter, fixed carbon, and ash results showed that the recovered residues of E. saligna were more susceptible to variations in minimum stem diameters, with up to 53% reduction in ash content between the smallest diameter and full trees. Higher and lower heating values showed non-statistical differences between the minimum stem diameters in Eucalyptus stands.